Conservation status and growth response of cnidoscolus aconitifolius (mill.) johnst. to fertilizer in Ibadan, South-western Nigeria (2021)
Cnidoscolus aconitifolius (Mill.) Johnst., is a domesticated leafy vegetable. Knowledge of its ethnobotanical use, growth biology under soil amendments, and acceptability is insufficient in southwest Nigeria. The study evaluated its response to soil amendments and conservation potential in metropolitan and agrarian local government areas (LGAs) of Ibadan, Nigeria. The study was conducted in the Crop Garden of the Department of Crop Protection and Environmental Biology, University of Ibadan (N07.451655, E003.89708), and in six agrarian and five metropolitan LGAs. The growth experiment consisted of four treatments: A no-amendment control, cattle dung, poultry manure, and NPK15:15:15 replicated thriceand laid out in a completely randomized design. Data were collected on plant height, the number of leaves, stemdiameter, total leaf area, and number of branches. They were analysed using analysis of variance (ANOVA) with significant means separated by Fisher's LSD (p=0.05). A structured questionnaire was administered using the snowballing procedure. Data were descriptively and inferentially analysed. No significant difference was observed between plant heights of no-amendment control and other treatments. NPK 15:15:15 treatments had the lowest mean number of leaves. Stem cuttings planted in amended soils had lower diameters (1.5 cm, 1.7 cm, 1.3 cm for no-amendment control, poultry manure, and cattle dung respectively) in 10 weeks after sowing compared to the control (2.0 cm). Similar trend was observed for total leaf area. Amendments with poultry manure gave the highest mean number of branches at 10 weeks after sowing, followed by NPK 15:15:15 while cattle dung had the lowest mean number of branches. A correlation coefficient (1.00) indicated perfect positive relationship between ages of respondents and viewed that its cultivation would mitigate climate change impact in Ibadan. Farmers would consider cultivating it. The potential conservation preference (á =0.295) of the crop among younger respondents could (0.05) confer protection on it. The study revealed that Cnidoscolus aconitifolius can develop to its full potential with little or no soil amendments, probably being a deep-rooting plant. The awareness among residents in Ibadan could ensure its conservation. In addition, the cultivation should be encouraged as a low-input vegetable to ameliorate food insecurity